Absorption mechanism of oxymatrine in cultured Madin–Darby canine kidney cell monolayers. (2nd October 2016) - Xiong, Xiao-Hong; Huang, Li-Hua; Zhong, Yun-Ming; Cheng, Xuan-Ge; Cen, Mei-Feng; Wang, Gui-Xiang; Zang, Lin-Quan; Wang, Su-Jun
Abstract: Context Oxymatrine (OMT) is beneficial to human health by exerting various biological effects.Objective To investigate the absorption mechanism of OMT and discover absorption enhancers using Madin–Darby canine kidney (MDCK) cell monolayers. Materials and methods Concentration effects on the transport of OMT were measured in the range of 1.0 × 10 −5 –1.0 × 10 −3  M in 2 h. Then, the effect of time, direction, temperature and pH on the transport of OMT at 10 −4 M was studied. Moreover, P app of OMT was determined in the absence/presence of cyclosporine and surfactants at 100 μM to further confirm the relative transport mechanism. Results The P app AP→BL ranged from (3.040 ± 0.23) × 10 −6 to (3.697 ± 0.19) × 10 −6  cm/s as the concentration varied from 10 −5 to 10 −3 M. OMT showed similar P app at 4 and 37 °C ( p  > 0.05). Increasing the apical pH 7.4 and 8.0 resulted in P app versus pH 5.0 ( p  < 0.01). Furthermore, in the presence of cyclosporine and surfactants including sodium citrate, sodium dodecyl sulphate (SDS) and deoxysodium cholate, P app was (0.318 ± 0.033) × 10 −5, (0.464 ± 0.048) × 10 −5, (0.897 ± 0.115) × 10 −5 and (1.341 ± 0.122) × 10 −5  cm/s, respectively. In the presence of surfactants, P app significantly increased up to 1.5–4.3-fold ( p  < 0.05). Discussion and conclusion OMT transport across MDCK cell monolayers was by passive diffusion. Sodium citrate, SDS and deoxysodium cholate serve as excellent absorption enhancers which are useful for the related research improving the oral bioavailability of OMT.